Amid Guatemala’s faltering democracy, a battle to remember its painful past - Geneva Solutions - Langrand, Michelle (Geneva Solutions, 2023)
As Guatemalans head to the polls on Sunday, decades of struggle for justice for atrocities committed during the civil war hang in the balance. Paulo Estrada Velásquez was one year and 20 days old when his father went missing on 19 May 1984 in Guatemala. No more than a month later, his uncle would also vanish. They were both members of Guatemala’s communist party, Partido Guatemalteco del Trabajo, and two of around 40,000 people who were forcibly disappeared during Guatemala’s civil war.
Guatemala
Keywords: 2023-06 June